ANALISIS RASIO CAMEL TERHADAP PREDIKSI KONDISI BANK BERMASALAH DI INDONESIA (Students' Journal of Accounting and Banking, 2012)
This research aimed to analyze the bank's financial ratios to predict problem banks in Indonesia. Variables used a seven-bank financial ratios namely CAR, NPL, ROA, LDR, ROE, BOPO and NIM. The research data obtained in the census which shall mean the entire population used in the research, amounting to 123 banks in the years 2007-2009. Analysis tool used is the logit regression.The results of multivariate tests showed that the CAR, NPL, ROA, LDR, ROE, and NIM BOPO not significantly affect the probability of the condition of troubled banks in Indonesia. The accuracy of prediction of the condition of troubled banks by 94.1% in 2007-2009.Keywords: CAMEL, Condition Bank, CAR, NPL, ROA, LDR, ROE, BOPO and NIM